2019
DOI: 10.1088/1758-5090/ab52ea
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mechanics of 3D-printed scaffolds by crystal lattice-like structural design for breast tissue engineering

Abstract: Breast tissue engineering is a promising alternative to standard treatments for breast defects. Although there is a consensus that the mechanical property of the scaffold should best match the reconstructed tissue, the simulation of the soft and elastic tactility of native breast tissues using conventional materials and architecture design requires further study. Previous research has shown that the crystal microstructure-like design can drastically alter the mechanical properties of the constructed scaffolds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Highly controlled lattice architectures are seeing growing interest in different application fields, ranging from the manufacturing of lightweight orthosis [1][2][3], scaffolds for tissue engineering [4][5][6][7][8][9][10][11], implantable medical devices [12][13][14], stimuli-responsive softrobotics [15][16][17], and topology optimization for architectural structures [18]. Such lattice structures comprise a base form, namely unit cell, which is spatially repeated across the entire structure either in a fixed x, y, z geometry or with varying degrees of asymmetry [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Highly controlled lattice architectures are seeing growing interest in different application fields, ranging from the manufacturing of lightweight orthosis [1][2][3], scaffolds for tissue engineering [4][5][6][7][8][9][10][11], implantable medical devices [12][13][14], stimuli-responsive softrobotics [15][16][17], and topology optimization for architectural structures [18]. Such lattice structures comprise a base form, namely unit cell, which is spatially repeated across the entire structure either in a fixed x, y, z geometry or with varying degrees of asymmetry [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…TPU materials and 3D printing technology were selected to construct diamond-shaped (N5S4) breast scaffolds. Our previous study demonstrated that the scaffolds with N5S4 architecture that mimic the lattice microstructure of diamond are soft and resilient enough for breast reconstruction [ 24 ]. Since the ratio of 0.5 × 10 6 hUCMSCs to 0.5 ml fat achieves the highest volume retention rate of the graft among all three concentrations and the diameter of the breast scaffold is 1 cm depending on the size of the nude mice, we injected 0.2 ml of fat.…”
Section: Discussionmentioning
confidence: 99%
“…In the hUCMSC groups, mice were implanted subcutaneously using the same method on each side of the back with scaffold filled with 0.2 ml of human fat and 20 µl of sterile saline containing 0.2 × 10 6 hUCMSCs. The material and architecture of scaffold in the present study refer to our previous research [ 24 ]. The scaffold is built with N5S4 architecture which mimic the lattice microstructure of diamond are soft and resilient enough for breast tissue engineering, which has showed considerable advantages in animal study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued efforts are needed to investigate in vivo biotoxicity, biodegradability, and mechanical performance to open the way for clinical applications (Zhou et al 2019).…”
Section: Cartilage Regeneration Scaffoldsmentioning
confidence: 99%